2015
DOI: 10.2991/ict4s-env-15.2015.6
|View full text |Cite
|
Sign up to set email alerts
|

GIS-based Life Cycle Assessment of urban building stocks retrofitting- a bottom-up framework applied to Luxembourg

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Based on GIS analysis and (Geo Da) techniques as followed in LCA assist in communicating information with stakeholders (i.e., environmental organizations, communities, interested and affected parties, and authorities). The integration of GIS in LCA tool is capable to localize impact sources to organize spatial data especially at large scale; develop spatial inventory models and visualize results for stakeholders [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on GIS analysis and (Geo Da) techniques as followed in LCA assist in communicating information with stakeholders (i.e., environmental organizations, communities, interested and affected parties, and authorities). The integration of GIS in LCA tool is capable to localize impact sources to organize spatial data especially at large scale; develop spatial inventory models and visualize results for stakeholders [15].…”
Section: Discussionmentioning
confidence: 99%
“…Also, GIS offers the opportunity to manage and automatically process information at larger scales taking into account the spatial dimension and achieving a higher level of detail. GIS capacity to tackle huge spatial databases may support LCA at the territorial scale and reduce the working time to perform the LCA studies in the future [15].…”
Section: Methodsmentioning
confidence: 99%
“…GIS are based on the combination of spatial data with several attributes and have been demonstrated as effective interdisciplinary tools [28]. Batty and Xie [29] indicated that GIS technology provides the basic framework for processing large volumes of spatial data, obtaining georeferenced information, and producing visual and easily updatable results; therefore, these systems are ideal for creating models that incorporate the attributes of individual buildings [20,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of Geographical Information Systems (GIS) to create geospatial data models in this new building-by-building approach has been explored in recent studies [10,11]. The combination of geospatial models and LCA at the urban scale has recently been developed by Mastrucci et al to the Luxemburg context [12].…”
Section: Introductionmentioning
confidence: 99%